Association of frailty with non-laboratory based cardiovascular disease risk score among older adults and elderly population: insights from longitudinal aging study in India (LASI-1st wave) - Pritam Halder; Semanti Das; Anshul Mamgai; Divya Sharma; Ashish Behera; Pulak Syal; Vineeth Rajagopal; Tanvi Kiran (BMC Public Health)
Abstract Introduction Frailty is an inevitable part of ageing, which is also associated with a variety of chronic diseases, the most common of which are cardiovascular diseases. The WHO non-laboratory-based CVD risk scores are reliable predictors of cardiovascular events and are used in treatment decision-making in primary health-care settings. The current study aims to find the association between the non-laboratory-based CVD risk scores and frailty scores. Methods The association between frailty and CVD risk scores of 56,450 older adults was estimated using nationally representative survey (Longitudinal Aging Study in India -LASI-1st Wave). Separate multivariable logistic regression was performed after adjusting for socio-economic, demographic and health related variables. Restricted cubic splines were also estimated to explore the association between probability of frailty and non-lab-based CVD risk score. Results The mean age of the participants was 59.3 ± 10.3 years. The prevalence of frailty was 15.6% in the participants above 45 years and 25.5% among participants aged more than 60 years. There was a significant association between the CVD risk scores and frailty in the participants and an increasing trend across the age groups (aOR = 1.3 (1.1–1.4), 2.3 (1.1–2.6), 3.6 (3.1–4.2) and 5.0 (2.9–8.6)) for CVD scores of 5–9, 10–19, 20–29 and > 30 respectively compared to a CVD risk score of < 5. The strength of association of frailty with CVD risk score when adjusted for both socioeconomic, demographic and health variables (model 2), was greater for females and ≥ 60 years age groups (aOR = 19.9 (CVD score > 30) and 4.6 (CVD score 20–29), respectively). Conclusion Screening for frailty should be performed in individuals with high non-laboratory-based CVD risk scores as a method of primary prevention to plan targeted interventions as a form of secondary prevention with more focusing on females and ≥ 60 years elderly population.